Coalescence preference dynamics for droplet growth during single-component fluid phase separation - Singh, Juhi; Roy, Sutapa (Frontiers in Physics, 2022)
When two unequal sized droplets coalesce to form a final product drop, the product forms closer to the larger of its two parents -- a phenomenon known as the coalescence-preference dynamics. In this paper, using the state-of-the-art molecular dynamics simulations, we study the time-dependent properties of coalescence preference for phase segregating single-component fluids, over a broad range of fluid density and temperature. Hydrodynamics is fully taken into account. Coalescence time is observed to be shorter for parents with larger size ratio. Our simulation data also points towards an interesting power-law dependence of the coalescence time on the droplet size ratio, which is universal for both droplets and microbubbles.